Analytical model of moment-rotation relation for steel beam to CFST column connections with bidirectional bolts. (1st October 2019) - Zhou, Guojie; An, Yonghui; Li, Dongsheng; Ou, Jinping
Highlights: A practical analytical model of moment-rotation relation for SBCFSTCCBB is proposed. It is simple and convenient since it avoids workloads of simulations and experiments. A method for calculating ultimate moment resistance of SBCFSTCCBB is proposed. Failure mode of SBCFSTCCBB can be predicted using the ultimate moment resistance. Abstract: The steel beam to concrete filled steel tube (CFST) column connection with bidirectional bolts has good seismic performance, and it plays an important role in the semi-rigid composite frame. The moment-rotation relation is indispensable in the design of this connection; however, the current moment-rotation relation models require experimental or simulation data to fit their shape parameters and physical parameters, which results in large cost of time, economy, human resource and material resource. Therefore, a practical analytical model for the moment-rotation relation of this connection, i.e. the ultimate moment resistance and initial rotational stiffness based two-parameter exponential model, is proposed. With consideration of the possible failure modes, calculation methods for predicting ultimate moment resistance is developed using dimension parameters and material properties of the connection without any experimental or simulation data. Prediction results based on the proposed analytical model of moment-rotation relation and calculation methods of ultimate moment resistance show good agreements with experimental results, and the failure mode of this connection can also be predicted well. The proposed analytical model can be used in the design and structural analysis of the semi-rigid composite frames to predict the moment-rotation relation accurately; moreover, the proposed model avoids the workload of simulations and experiments, which is simple and convenient for engineers.